Evaluation of Project Budget Due to Price Fluctuations Based on Digital Technology in Factory Construction Projects - Citra, Zel; Wibowo, Paksi Dwiyanto; Malinda, Yosie (Universitas Negeri Padang, 2023)
The development of industrial construction requires adequate resources to avoid the failure and risk of the project. The resources required are materials (building materials), human resources (human resources), machines (equipment), capital (money), methods (methods of implementation), timing, and information on the implementation of the construction. According to data from the Central Statistical Agency (BPS), wages of labor in Indonesia of Rs. 2.89 million increased by 1.12% by 2022. In addition, the price of construction materials has also increased, such as steel, steel bones, concrete, and other construction materials. Especially steel price increases, starting in the second year of the pandemic, have risen about 30%–40%. Generally, the construction of factory buildings uses more steel profiles for the construction of warehouses—storage of raw materials or warehousing of production sites. This has a huge impact on the project budget that has been estimated prior to material price fluctuations. Therefore, the re-evaluation of the project budget in PT. XYZ, which has been estimated by the company at Rp. 219.5 billion, has a total budget change to Rp. 276.1 billion.